Analysis of citations in the theses collection of the College of Arts and Sciences Reading Center, New Era University - Sibug, Michael D.; Dizon, Leticia B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 1999)
Citation analysis, a bibliometric study was used to analyze the characteristics of 533 citations of 53 undergraduate theses at the College of Arts and Sciences Reading Center in the New Era University.
These characteristics are identified according to format, author, title, age and subject taking into account the most number of citations. Results showed that the monograph is the most cited format with 315 citations making up 59.10 percent of the total citations. The most cited author is Elizabeth Hurlock who garnered a citation score of 13. The total number of authors cited is 403. The most cited material/title was the Manila Bulletin, which received a total number of citations of 20. A total of 353 titles were recorded. Age, in years, was determined by subtracting the years of publication of the citing thesis from the cited material. Most of the citations were 1 year old (44 citations). The oldest material cited had an age of 90 years. The modal age group or class is 0 to 9 years (257 citations). Psychology is the general subject wherein most of the citations fall. It had 383 total citations, accounting for 71.86 percent of all the citations. Using the relational classification of data, the hypothesis that the monographs are the more cited format than the periodicals and unpublished materials was statistically significant.
Vita.
Computer print out.
Thesis (Bachelor of Library and Information Science)
Keywords: Bibliographic citations; Dissertations, Academic -- Philippines; New Era University.College of Arts and Sciences.Reading Center